Improving Interpersonal Speaking Learning Outcomes and Students’ Confidence as Well as Exploring Students’ Responses through Project-Based Learning - Mayekti, Meilina Haris; Faiza, Dinar; Bestari, Ade Christanty Yudha (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This project-based Classroom Action Research aims to improve students' speaking skills in the Interpersonal Speaking course, which are still low, and to enhance students' self-confidence. This research uses the Kemmis and McTaggart method and consists of 2 cycles. Planning, implementation, observation, and reflection are components in each cycle. This classroom action research was conducted two meetings in each cycle. The instruments used consisted of pre-test and post-test, questionnaires and observation sheets. The results of this study were analysed using simple statistical methods with the following outcomes: the pre-test score was 62 and the post-test score was 68 in the first cycle, while the pre-test score in the second cycle was 64 and the post-test score was 78. The students' confidence level also increased by 75% during the second cycle. This indicates an improvement in speaking skills, an increase in students' confidence, and a positive response to the material. After the method was used, the speaking learning outcomes in the Interpersonal Speaking course improved. Recommendations for this research include strengthening the implementation of PBL through relevant project designs, approaches to boost confidence, utilization of technology, evaluations based on student feedback, professional development for lecturers, and integration into the curriculum. By implementing these recommendations, it is expected that students' learning outcomes and their confidence in interpersonal speaking will improve, and their responses to the learning process will become increasingly positive.